(untitled) (Palíndromo, 2013)
This article covers the collective creative process in comics (HQs). Four different works are highlighted, produced by me, in partnership with several authors. The propose, then, is the creation and analisis of the envolved creative process, considering studies made by artistis, such as Fayga Ostrower and psicanalists, like Rollo May; between others. The intuit is to map and discuss the creative process of the authors, how they relate with each other to create a common sense and how the authorial comics matches the artistic product concept. We observe that, as spontaneous and conceitual realizations, the HQs are object of art as well as other human manifestations, separated only by limitant interpretations, once they require equal involvement of the author to so.